2018
DOI: 10.1101/299842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic and epidemiological monitoring of yellow fever virus transmission potential

Abstract: The yellow fever virus (YFV) epidemic that began in Dec 2016 in Brazil is the largest in decades. The recent discovery of YFV in Brazilian Aedes sp. vectors highlights the urgent need to monitor the risk of re-establishment of domestic YFV transmission in the Americas. We use a suite of epidemiological, spatial and genomic approaches to characterize YFV transmission. We show that the age-and sex-distribution of human cases in Brazil is characteristic of sylvatic transmission. Analysis of YFV cases combined wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(190 citation statements)
references
References 62 publications
2
102
0
8
Order By: Relevance
“…However, both the evidence of positive selection and the coincidence of the emergence of mutations and increased viral dissemination implies a potential positive impact on the spread of the virus [143,145]. Additional phylogenetic and epidemiological studies suggest that the transmission dynamics are primarily sylvatic, with multiple transmission cycles in NHPs, that could inadvertently result in increased human exposure to YFV, indicating a predominant role of NHP-mosquito-human rather than humanmosquito-human transmission during this epidemic [146,172]. Of note, in January, the Evandro Chagas Institute (Brazil) reported the detection of YFV in Ae.…”
Section: In South Americamentioning
confidence: 95%
“…However, both the evidence of positive selection and the coincidence of the emergence of mutations and increased viral dissemination implies a potential positive impact on the spread of the virus [143,145]. Additional phylogenetic and epidemiological studies suggest that the transmission dynamics are primarily sylvatic, with multiple transmission cycles in NHPs, that could inadvertently result in increased human exposure to YFV, indicating a predominant role of NHP-mosquito-human rather than humanmosquito-human transmission during this epidemic [146,172]. Of note, in January, the Evandro Chagas Institute (Brazil) reported the detection of YFV in Ae.…”
Section: In South Americamentioning
confidence: 95%
“…Besides that, delivery of circRNA using lipid nanoparticles and delivery of circRNA via exosomes can be used to overcome delivery challenges. For example, according to genome-wide RNA-seq research, Li et al found that exosomes are a rich source of circRNAs, and they were proven to be abundant in exosomes as compared to parental cells (Lener et al, 2015). Similarly, in a mouse model, Li and his team showed that circRNA can be successfully encapsulated and distributed into aggressive tumors by using lipid nanoparticles (Li et al, 2022b).…”
Section: Exosomal Circrnas As Potential Therapeutic Targets In Breast...mentioning
confidence: 99%
“…Because the age of the incidence of ureteral cancer is younger in clinical practice, and the location of the incidence is mostly between the bladder and the kidney, early diagnosis and treatment effect are very important (Nir et al, 2020). Clinically, it is necessary to comprehensively analyze and evaluate the tumor stage and pathological classification, the relationship between stage and clinical prognosis, and the prognosis between different stages, so as to obtain the best treatment plan suitable for the patient's condition.…”
Section: Detection and Prognostic Analysis Of Ureteral Carcinomamentioning
confidence: 99%